Investigation of the Learning Styles of Pre-Service Sports Teachers Enrolled at a Pedagogical Formation Program - Sabahattin DENİZ; Süleyman CAN (Institute of Advanced Engineering and Science, 2018)
The purpose of the current study is to investigate the learning styles of the students from the Faculty of Sports Sciences. These students are enrolled at the pedagogical formation program and attending different departments of the Faculty of Physical Education and Sports. The study is a descriptive study employing the general survey model. As the data collection tool, “Vermunt Learning Styles Scales (VLSS)” was used. The study group of the current research is comprised of Sports Sciences Faculty students enrolled at the pedagogical formation program at the Education Faculty of Muğla Sıtkı Koçman University in 2016-2017 academic year. The findings of the study revealed that while the re-service sports sciences teachers’ study activities (information processing and organization) and study motives (mental model of learning and learning orientation) do not vary significantly depending on gender, age, branch, the state of having a coaching license or not and the state of working in a job or not, they vary significantly depending on department (coaching, sports management, recreation, physical education and sports teaching) and general academic achievement